Delivery of a stringent dimerizer-regulated gene expression system in a single retroviral vector - Pollock, Roy (The National Academy of Sciences, 2000)
Small molecule-regulated transcription has broad utility and would benefit from an easily delivered self-contained regulatory cassette capable of robust, tightly controlled target gene expression. We describe the delivery of a modified dimerizer-regulated gene expression system to cells on a single retrovirus. A transcription factor cassette responsive to the natural product dimerizer rapamycin was optimized for retroviral delivery by fusing a highly potent chimeric activation domain to the rapamycin-binding domain of FKBP-rapamycin-associated protein (FRAP). This improvement led to an increase in both the potency and maximal levels of gene expression induced by rapamycin, or nonimmunosuppressive rapamycin analogs. The modified transcription factor cassette was incorporated along with a target gene into a single rapamycin-responsive retrovirus. Cell pools stably transduced with the single virus system displayed negligible basal expression and gave induction ratios of at least three orders of magnitude in the presence of rapamycin or a nonimmunosuppressive rapamycin analog. Levels of induced gene expression were comparable to those obtained with the constitutive retroviral long terminal repeat and the single virus system performed well in four different mammalian cell lines. Regulation with the dimerizer-responsive retrovirus was tight enough to allow the generation of cell lines displaying inducible expression of the highly toxic diphtheria toxin A chain gene. The ability to deliver the tightly inducible rapamycin system in a single retrovirus should facilitate its use in the study of gene function in a broad range of cell types.